Effect of hydraulic retention time on metal precipitation in sulfate reducing inverse fluidized bed reactors. Issue 1 (13th February 2014) - Villa Gomez, Denys Kristalia; Enright, Anne Marie; Rini, Eki Listya; Buttice, Audrey; Kramer, Herman; Lens, Piet
Abstract BACKGROUND Metal sulfide recovery in sulfate reducing bioreactors is a challenge due to the formation of small precipitates with poor settling properties. The size of the metal sulfide precipitates with the change in operational parameters such as pH, sulfide concentration and reactor configuration has been previously studied. The effect of the hydraulic retention time (HRT) on the metal precipitate characteristics such as particle size for settling has not yet been addressed. RESULTS The change in size of the metal (Cu, Zn, Pb and Cd) sulfide precipitates as a function of the HRT was studied in two sulfate reducing inversed fluidized bed (IFB) reactors operating at different chemical oxygen demand concentrations to produce high and low sulfide concentrations. The decrease of the HRT from 24 to 9 h in both IFB reactors affected the contact time of the precipitates formed, thus making differences in aggregation and particle growth regardless of the differences in sulfide concentration. Further HRT decrease to 4.5 h affected the sulfate reducing activity for sulfide production and hence, the supersaturation level and solid phase speciation. Metal sulfide precipitates affected the sulfate reducing activity and community in the biofilm, probably because of the stronger local supersaturation causing metal sulfides accumulation in the biofilm. CONCLUSIONS This study shows that the HRT is an important factor determining the size and thus the settling rate of the metal sulfides formed in bioreactors. © 2013 Society of Chemical Industry